1995
DOI: 10.1002/anie.199500931
|View full text |Cite
|
Sign up to set email alerts
|

The Structural and Thermodynamic Basis for the Formation of Self‐Assembled Peptide Nanotubes

Abstract: Nanostructures through self‐assembly: Suitably designed planar cyclic peptides like 1 form cylindrical dimers in nonpolar organic solvents. These ensembles are good models for the fundamental description of parallel and antiparallel β‐sheet structures as well as for the design of novel peptide nanostructures. The analysis of the structural and thermodynamic aspects of the dimerization process showed that the hydrogen bonds between the peptide backbones are crucial factors for the stability of the ensembles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(182 citation statements)
references
References 32 publications
11
168
0
3
Order By: Relevance
“…Experimentally, when self-assembly occurs, not only would the dimer form, but the trimer and longer assemblies would also be present. The 1 H NMR and IR studies by Ghadiri et al 5 showed that cyclo [(-L-Phe-D-N-MeAla-) 4 -] displays several conformational isomers in polar solvents, such as deuterated methanol or dimethyl sulfoxide (DMSO), which slowly interconvert as a result of the cis-trans isomerization of secondary amides. This inhibits the dimerization process in polar solvent for the capped dimer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, when self-assembly occurs, not only would the dimer form, but the trimer and longer assemblies would also be present. The 1 H NMR and IR studies by Ghadiri et al 5 showed that cyclo [(-L-Phe-D-N-MeAla-) 4 -] displays several conformational isomers in polar solvents, such as deuterated methanol or dimethyl sulfoxide (DMSO), which slowly interconvert as a result of the cis-trans isomerization of secondary amides. This inhibits the dimerization process in polar solvent for the capped dimer.…”
Section: Resultsmentioning
confidence: 99%
“…5 It was found that the peptide subunit cyclo [(-L-Phe-D-N-MeAla-) 4 -] adopts a flat-ring-shaped conformation, which energetically favors ring stacking and intermolecular hydrogen-bonding interactions over the nonassembled form by 4.0-5.6 kcal mol -1 , depending on the solvent. The free energy of the dimerization process is accessible via steered MD (SMD) simulations using Crooks theorem 16,17 in the form of the Jarzynski equality.…”
Section: Introductionmentioning
confidence: 99%
“…Free energy of binding 15 The PMF curves obtained from the US simulations corresponding to the transport of 5FU through the WL and QAEA systems are given in Figure interaction. The energy barrier for the diffusion of the Na + ion through the CPNT is estimated as 2.0 kcal/mol.…”
Section: Hydrophobic Interactionsmentioning
confidence: 99%
“…[8][9][10][11][12] Depending on the hydrophilic or hydrophobic nature of the side chain of amino acids, the cyclic peptide nanotubes can be found either in water solution or in lipid bilayers. Due to their properties related to ion transport, they have been considered to be an antibacterial agent or a potential ion sensor.…”
Section: Introductionmentioning
confidence: 99%